2004
DOI: 10.1002/jms.515
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of α‐ and γ‐glutamyl dipeptides by negative ion collision‐induced dissociation

Abstract: The low-energy CID mass spectra of the [M-H](-) ions of a variety of dipeptides containing glutamic acid have been obtained using cone-voltage collisional activation. Dipeptides with the gamma-linkage, H-Glu(Xxx-OH)-OH, are readily distinguished from those with the alpha-linkage, H-Glu-Xxx-OH, by the much more prominent elimination of H-Xxx-OH from the [M-H](-) ions of the former isomers, resulting in formation of m/z 128, presumably deprotonated pyroglutamic acid. Dipeptides with the reverse linkage, H-Xxx-Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…It is generally observed for protonated peptides that the only exchangeable hydrogens are those attached to heteroatoms [4,9]. For deprotonated peptides, however, some C-bonded hydrogens are also mobilized during the activation process [25][26][27]. The predominant backbone cleavage in the present study is an N-C ␣ cleavage at an Asp residue.…”
Section: Discussionmentioning
confidence: 50%
“…It is generally observed for protonated peptides that the only exchangeable hydrogens are those attached to heteroatoms [4,9]. For deprotonated peptides, however, some C-bonded hydrogens are also mobilized during the activation process [25][26][27]. The predominant backbone cleavage in the present study is an N-C ␣ cleavage at an Asp residue.…”
Section: Discussionmentioning
confidence: 50%
“…The daughter ion at m/z 224 might be produced by hydrogen/deuterium back-exchange of d 1 -labeled ion m/z 225 in ion trap [34] or by loss of a molecule of CH 2 DOD through a interchange of carbon-bonded hydrogens with labile hydrogens during the fragmentation reactions. [35] Meanwhile, the (Fig. 3B, entry 2).…”
Section: Positive-ion Esi-ms N Of the Protonated N-map-aasmentioning
confidence: 96%
“…In our initial study 18 of deprotonated peptides containing only H or alkyl side chains, we observed that there was more extensive sequence-specific fragmentation under low-energy CID conditions than under high-energy CID conditions. 21 We have extended these studies to deprotonated peptides containing phenylalanine 22 and to deprotonated peptides containing glutamic acid; 23 in both cases fragmentation reactions specific to the side chain functionality were observed. In the present work, we explore…”
Section: Introductionmentioning
confidence: 94%